Randomised study of six beta-blockers and a thiazide diuretic in essential hypertension - Wilcox, R G (1978)
Atenolol was compared with five other beta-blockers and a thiazide diuretic in a randomised cross-over trial of once-daily treatment of essential hypertension. Atenolol was significantly better at reducing resting and exercise blood pressures at 24 hours than any of the other drugs and had a low incidence of side effects. Both timolol and acebutolol had a significant hypotensive effect at 24 hours and a low incidence of side effects, suggesting that further increases in dosage might be effective and well tolerated. Labetalol proved ineffective when given once daily, and the high incidence of side effects, equalled only by pindolol, would probably prohibit further increases in dosage. Bendrofluazide was equal or superior to all the beta-blockers except atenolol at reducing resting blood pressure, and its cheapness still makes it an agent of first choice in mild or moderate essential hypertension.